Analisis Kualitatif Health Belief Model terhadap Keinginan Berhenti Merokok pada Mahasiswa Laki-Laki Fakultas Xxx Universitas Yyy - El Vinta Rahmi; Adila Kasni Astiena; Husna Yetti (Universitas Pahlawan Tuanku Tambusai, 2026)
Smoking among health students reflects a gap between academic knowledge and personal health behavior. This article reports the qualitative component of a study that explored Health Belief Model constructs related to the intention to quit smoking among male students at Faculty xxx, University yyy. A qualitative descriptive approach was used through semi-structured in-depth interviews with 15 male student smokers from aaa, bbb, and ccc study programs, supported by one key institutional informant. Informants were selected using snowball sampling because smoking behavior in the campus context was sensitive and not formally recorded. Data were analyzed thematically through data reduction, data display, and conclusion drawing. The findings showed that students understood the health risks and severity of smoking, but perceived susceptibility was not always internalized personally. The perceived benefits of quitting included improved health, better stamina, psychological relief, economic savings, and professional credibility as future health workers. However, nicotine dependence, craving, academic stress, emotional regulation, peer pressure, and smoking routines were strong barriers to quitting. Cues to action emerged from family reminders, health information, clinical exposure, and smoke-free campus rules, while self-efficacy remained unstable. The study highlights that smoking cessation interventions should go beyond risk education by integrating psychological support, peer-based assistance, personal risk communication, and consistent institutional policy.